Ultrasmall Manganese Ferrites for In Vivo Catalase Mimicking Activity and Multimodal Bioimaging. Issue 16 (8th March 2022) - Carregal‐Romero, Susana; Miguel‐Coello, Ana Beatriz; Martínez‐Parra, Lydia; Martí‐Mateo, Yolanda; Hernansanz‐Agustín, Pablo; Fernández‐Afonso, Yilian; Plaza‐García, Sandra; Gutiérrez, Lucía; Muñoz‐Hernández, María del Mar; Carrillo‐Romero, Juliana; Piñol‐Cancer, Marina; Lecante, Pierre; et al.
Abstract: Manganese ferrite nanoparticles display interesting features in bioimaging and catalytic therapies. They have been recently used in theranostics as contrast agents in magnetic resonance imaging (MRI), and as catalase‐mimicking nanozymes for hypoxia alleviation. These promising applications encourage the development of novel synthetic procedures to enhance the bioimaging and catalytic properties of these nanomaterials simultaneously. Herein, a cost‐efficient synthetic microwave method is developed to manufacture ultrasmall manganese ferrite nanoparticles as advanced multimodal contrast agents in MRI and positron emission tomography (PET), and improved nanozymes. Such a synthetic method allows doping ferrites with Mn in a wide stoichiometric range (Mn x Fe3‐ x O4, 0.1 ≤ x  ≤ 2.4), affording a library of nanoparticles with different magnetic relaxivities and catalytic properties. These tuned magnetic properties give rise to either positive or dual‐mode MRI contrast agents. On the other hand, higher levels of Mn doping enhance the catalytic efficiency of the resulting nanozymes. Finally, through their intracellular catalase‐mimicking activity, these ultrasmall manganese ferrite nanoparticles induce an unprecedented tumor growth inhibition in a breast cancer murine model. All of these results show the robust characteristics of these nanoparticles for nanobiotechnological applications. Abstract : Ultrasmall manganese ferrite nanoparticles with variable Mn doping can be produced through a microwave‐assisted one‐pot method. The versatility of this synthetic method allows obtaining a library of different nanoparticles with advanced features in multimodal imaging (MRI/PET/CT) and catalase‐mimicking activity for nanobiotechnological applications in vitro and in vivo.